Population Pharmacokinetic Model of AST-001, L-Isomer of Serine, Combining Endogenous Production and Exogenous Administration in Healthy Subjects - Lee, Soyoung; Hwang, Su-Kyeong; Nam, Hee-Sook; Cho, Jung-Sook; Chung, Jae-Yong (Frontiers in Pharmacology, 2022)
AST-001 is an isomer of non-essential amino acids that has protective effects in neurological disorders. This study aimed to establish a population pharmacokinetic (PK) model of AST-001 in healthy Korean to further propose a fixed-dose regimen in pediatrics. The model was constructed using 648 plasma concentrations from 24 healthy subjects, including baseline endogenous levels during 24 h and concentrations after a single dose of 10, 20, and 30 g of AST-001. For the simulation, an empirical allometric power model was applied to the apparent clearance and volume of distribution with body weight. The PK characteristics of AST-001 after oral administration were well described by a two-compartment model with zero-order absorption and linear elimination. The endogenous production of AST-001 was well explained by continuous zero-order production at a rate of 0.287 g/h. The simulation results suggested that 2 g, 4 g, 7 g, 10 g, and 14 g twice-daily regimens for the respective groups of 10–14 kg, 15–24 kg, 25–37 kg, 38–51 kg, 52–60 kg were adequate to achieve sufficient exposure to AST-001. The current population PK model elucidated both endogenous production and exogenous administration of AST-001 and suggested an optimal fixed-dose regimen with five weight ranges in pediatrics for the upcoming phase 2 trial.